Penguatan Jiwa Enterpreneur Santri Melalui Program Membatik Di Pondok Pesantren Ar-Rifa’iyah Saronggi Sumenep - Fitriyah, Eliyatul; Sa’diyah, Halimatus; Erdiyani, Fenny (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study originates from the recognition of the important role of pesantren as institutions that not only educate students in religious matters but also contribute to economic empowerment and the preservation of local culture, as reflected in the batik training program at Pondok Pesantren Ar-Rifa’iyah Saronggi Sumenep. The research aims to describe and analyze how this batik program fosters students’ entrepreneurial spirit while strengthening character values and creative economic potential rooted in Madurese cultural traditions and Islamic principles. This study employs a qualitative approach using a field research design. The researcher collected data through interviews, observations, and documentation involving the pesantren leaders, batik instructors, students, alumni, and consumers of the students’ batik products, and then systematically analyzed the data to identify relevant patterns. The findings reveal that the batik program operates through stages of strengthening cultural and Islamic values, providing technical training, guiding production processes, establishing industrial partnerships, and facilitating product marketing. These stages not only enhance students’ technical skills but also shape their character to become creative, disciplined, independent, responsible, and socially aware individuals. The integration of Islamic education, the creative economy, and local culture positions the batik activities as an effective model for developing santripreneurs in line with the concept of Islamic Entrepreneurship, with strong potential for replication in other pesantren across Indonesia